Ultrasmall Dual-Band Metamaterial Antennas Based on Asymmetrical Hybrid Resonators - Ji-Xu Zhu; Peng Bai; Jia-Fu Wang (International Journal of Antennas and Propagation)
A new type of hybrid resonant circuit model is investigated theoretically and experimentally. The resonant model consists of a right hand (RH) patch part and a composite right and left handed (CRLH) part (RH + CRLH), which determines a compact size and also a convenient frequency modulation characteristic for the proposed antennas. For experimental demonstration, two antennas are fabricated. The former dual-band antenna operating at f-1=3.5 GHz (Wimax) and f+1=5.25 GHz (WLAN) occupies an area of 0.21λ0×0.08λ0, and two dipolar radiation patterns are obtained with comparable gains of about 6.1 and 6.2 dB, respectively. The latter antenna advances in many aspects such as an ultrasmall size of only 0.16λ0×0.08λ0, versatile radiation patterns with a monopolar pattern at f0=2.4 GHz (Bluetooth), and a dipole one at f+1=3.5 GHz (Wimax) and also comparable antenna gains. Circuit parameters are extracted and researched. Excellent performances of the antennas based on hybrid resonators predict promising applications in multifunction wireless communication systems.